Influence of obesity on the functioning of adults - Grochowska, Aneta; Kołpa, Małgorzata; Musiał, Zofia (Nursing Problems / Problemy Pielęgniarstwa, 2010)
Introduction. Universally an obesity, for which the increase is increasing with the age is a phenomenon appearing in final years. This state is a result of improper feeding and the restricted physical initiative. The obesity additionally is increasing health complaints appearing at older persons, considerably influencing the state of health and the quality of life. Aim of the study. Getting to know the influence of chosen dietary habits on the body weight (BMI indicator) amongst persons in the older century, analysis of the taken energetic attitude to life, assessment of the level of the knowledge concerning the influence of the obesity on the health. Material and methods. They conducted research in December of 2007, in the Commune Centre of Medical Services in the Lisia Góra (Małopolskie Province). Fifty persons constituted the research group in the century above 45. of year of the life. An age constituted the criterion of the selection of respondents (> 45.) and BMI (> 25). An author’s questionnaire form of the questionnaire form was a research tool. On the basis of conducted measurements of the height and the body weight examined, BMI was calculated. Results. Calculated BMI confirmed appearing second and third degree obesities at 0.55 men and 0.30 women and the first degree obesity at 0.40 women and 0.15 men. According to 0.50 men and 0.47 women a tendency to the exaggerated food was a main cause of the obesity. The majority of respondents led the sitting lifestyle (of 0.40 men and 0.53 women). Respondents proposed connected overweight problems i.e. fast tiring oneself - 0.48, breathlessness - 0.32, pains of the spine - 0.18. Conclusions. Lack of a physical effort at older persons and wrong dietary habits, they cause the bad physical fitness, they are reducing the general function of the organism, causing the excess weight and the obesity. With result of it limiting in moving, increasing pain complaints, and hence the deterioration are quality of life.